Breast cancer survival trends in different stages and age groups – a population-based study 1989–2013. (2nd January 2019) - Nordenskjöld, Anna E.; Fohlin, Helena.; Arnesson, Lars G.; Einbeigi, Zakaria; Holmberg, Erik; Albertsson, Per; Karlsson, Per
Abstract: Background: During the recent decades, breast cancer survival has gradually improved but there is limited knowledge on the improvement in population-based studies of patients diagnosed with different stages of the disease and in different age groups. Patients and methods: In two Swedish health care regions a total of 42, 220 female breast cancer patients below 90 years of age were diagnosed between 1989 and 2013. They were treated and followed according to national and regional guidelines and formed a population-based cohort. Results: Using patients diagnosed in 1989–1993 as a reference to the relative risk, 5-year mortality decreased with 49% for patients diagnosed at the end of the observation period (CI 95% 45–58). The mortality tended to decrease for patients with all stages of breast cancer and test for trend resulted in a statistically significant improvement over time in 5-year relative survival in stage III and IV and in 10-year survival in stage I and III. For each operable stage of disease, patients aged below 40 years or more than 70 years when diagnosed tended to have less favorable survival than patients diagnosed between 40–69 years of age. Test for trend resulted in statistically significant improvements over time for patients diagnosed at ages below 40, 40–54 and 54–69, but less marked improvements for patients older than 70 when diagnosed. Conclusions : During the period 1989–2013 the relative risk of 5-year mortality decreased with 49%. Improvements were seen in all age groups but were unevenly distributed between stages and age groups pointing to the need for further improvements for younger and elderly patients.